Anatomically orthogonal QRS electrocardiogram of the baboon (Papio hamadryas) and the macaque (Macaca mulatta). Sex and species differences - Ruttkay-Nedecký, I; Cherkovich, G M (Physiologia Bohemoslovaca, 1977)
Peak amplitudes of the QRS complex were evaluated in 28 adult macaques (Macaca mulatta) and 28 adult baboons (Papio hamadryas), using two anatomically orthogonal lead systems. The anteroposterior (z) and the transversal (x) component of the cardiac electric field was smaller in females than in males. Comparison of QRS amplitudes in baboons and macaques indicates that the loop of the spatial vectorcardiogram is situated further ventrally and to the right in the former. The relationship between ventrally and dorsally oriented cardiac vectors, in both baboons and macaques, displays a prevalence of ventrally oriented vectors compared with man, in whom this type of relationship is normally not found after the second year of life.
Keywords: sexuální faktory; mužské pohlaví; elektrokardiografie; Electrocardiography; ženské pohlaví; druhová specificita; zvířata; Macaca; Haplorrhini; Female; Haplorhini; Male; Sex Factors; Papio; Macaca mulatta; Species Specificity; Animals